KONTRIBUSI DISIPLIN BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SIMULASI DIGITAL - Rosidi Rayanti; Almasri Almasri (Universitas Negeri Padang, 2019)
The objectives to be achieved in the study are as follows: 1) to find out the magnitude of the contribution of learning discipline and the school environment together on the learning outcomes of digital simulation of class X TKR students at SMK 1 BenerMeriah. 2) To find out the magnitude of the discipline of learning contributions to the learning outcomes of digital simulation of class X TKR students at SMK Negeri 1 BenerMeriah. 3) to find out the size of the contribution of the school environment to the learning outcomes of digital simulation in class X TKR SMK Negeri 1 BenerMeriah. The research method is based on a theory, expert ideas or understanding of research based on experience, then developed into problems that are proposed to obtain justification (verification) in the form of empirical data support in the field. The form of quantitative research the author uses because to find out how the contribution of learning discipline and the school environment to the learning outcomes of digital simulations at SMK Negeri 1 BenerMeriah. The results of the learning discipline hypothesis and the school environment jointly contribute positively to the learning desirability of the digital simulation class X TKR at BenerMeriah Vocational High School 1 11.09%. Learning Discipline contributes to the learning outcomes of the TKR class X digital simulation at SMK Negeri 1 BenerMeriah 3.06%, the school environment contributes positively to the learning outcomes of the TKR class X digital simulation at BenerMeriah Vocational High School 10.30%.Keywords: Contribution of learning discipline, contribution of school environment, learning outcomes.